Immobilization of thermostable exo-inulinase from mutant thermophilic Aspergillus tamarii-U4 using kaolin clay and its application in inulin hydrolysis - Garuba, Emmanuel O. (J Genet Eng Biotechnol, 2018)
In this study, attempts were made to immobilize purified exo-inulinase from mutant thermophic Aspergillus tamarii-U4 onto Kaolinite clay by covalent bonding cross-linked with glutaraldehyde with an immobilization yield of 66% achieved. The free and immobilized inulinases were then characterized and characterization of the enzymes revealed that temperature and pH optima for the activity of the free and immobilized enzymes were both 65 °C and pH 4.5 respectively. The free inulinase completely lost its activity after incubation at 65 °C for 6 h while the immobilized inulinase retained 16.4% of its activity under the same condition of temperature and incubation time. The estimated kinetic parameters K(m) and V(max) for the free inulinase as estimated from Lineweaver-Burk plots were 0.39 mM and 4.21 µmol/min for the free inulinase and 0.37 mM and 4.01 µmol/min for the immobilized inulinase respectively. Inulin at 2.5% (w/v) and a flow rate of 0.1 mL was completely hydrolysed for 10 days at 60 °C in a continuous packed bed column and the operational stability of the system revealed that the half-life of the immobilized inulinase was 51 days. These properties make the immobilized exo-inulinase from Aspergillus tamarii-U4 a potential candidate for the production of fructose from inulin hydrolysis.